ANALISIS KETIDAKKONDUSIFAN KELAS PADA PEMBELAJARAN MATEMATIKA BERBASIS PERMAINAN DI SEKOLAH DASAR DALAM PERSPEKTIF JOYFUL LEARNING - Nur Azizah, Lutfi; Sutrisno, Tri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the causes and forms of classroom disruption that emerged during a game-based mathematics lesson for second-grade students at SDN Geneng 02, and to examine the extent to which the practice reflects the principles of joyful learning. A qualitative descriptive case-study approach was employed, with data collected through structured observation of one classroom teacher and twenty second-grade students during a lesson on counting, reading, and writing numbers 51-100. Data were analyzed through data reduction, data display, and conclusion drawing. The findings show that the use of concrete media (straws and a number board) combined with a game-based worksheet (